VARIABILITY STUDIES IN SEGREGATING POPULATIONS OF RICE (ORYZA SATIVA L.) - PANWAR, L.L.; MATHUR, S.S. (Annals of Agricultural Research, 2014)
Genetic parameters were studied in a set of thirteen parental lines and thirty F2 populations in transplanted rice. For all the characters, the estimates of GCV were smaller than that of PCV, suggesting the influence of environment on them. High heritability coupled with high genetic advance for filled grains panicle-1, harvest index, grain yield panicle-1, productive tillers plant-1 and biological yield plant-1 indicated that these characters were predominantly governed by additive gene action and improvement for these characters could be brought about by direct selection. High heritability with moderate to low genetic advance for days to 50% flowering, panicle length, spikelet fertility and 1000-grain weight suggested the predominant role of non-additive gene action in their inheritance and selection for these characters must be taken up in advance generations.